Melatonin as a Multipotent Component of Fish Feed: Basic Information for Its Potential Application in Aquaculture - Acharyya, Akash; Das, Joydeep; Hasan, Kazi Nurul (Frontiers in Marine Science, 2021)
Melatonin (N-acetyl-5-methoxy-tryptamine), a pineal hormone, is synthesized from aromatic amino acid L-tryptophan but it is also produced by other non-pineal tissues in fish including entero-chromaffin cells of gastro-intestinal tract. One of the distinct characteristics of this hormone is its rhythmic synthesis in the gut and its release in circulation in all studied vertebrates. So, gut melatonin has a major contribution to supply a large amount of melatonin to other peripheral organs. Because of its pleiotropic action, and functional participation in physiological processes ranging from neuroendocrine to immune systems and growth to reproduction, it is successfully used in aquaculture. Recently, many studies have been analyzed the results of the use of L-tryptophan to stimulate gut melatonin synthesis which finally increases the production of freshwater and marinewater fish in culture. However, it is a potent indolamine that effectively stimulates the activity of the protein, carbohydrate, and lipid digesting enzymes in fish. It also plays a major protective role in fish due to its antioxidative role against cellular stress and pathogenic bacterial infection in gastric ulcer. Currently, available data also suggested that this hormone may be used as a hormonal tool to increase the production of healthy male and female fish seed which is an important factor in aquaculture. Now, the use of L-tryptophan as a precursor of melatonin or application of melatonin directly in fish food is an interesting research topic to validate its significance in aquaculture. So, the present review will focus the relevance of melatonin as fish food component to augment the quality of aquaculture system by modulating the physiological functions.